2017
DOI: 10.1016/s2542-5196(17)30118-3
|View full text |Cite|
|
Sign up to set email alerts
|

Urban greenness and mortality in Canada's largest cities: a national cohort study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
145
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(164 citation statements)
references
References 24 publications
14
145
3
2
Order By: Relevance
“…In summary, evidence for the relationship between higher levels of greenness and lower mortality strengthened considerably with the addition of large prospective cohort studies corroborating previous findings [23,51,52], although it should be noted that the evidence is not entirely consistent [53]. In addition, a study in Europe and another in Asia showed that greenness may attenuate associations between extreme heat and mortality [54,55].…”
Section: Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…In summary, evidence for the relationship between higher levels of greenness and lower mortality strengthened considerably with the addition of large prospective cohort studies corroborating previous findings [23,51,52], although it should be noted that the evidence is not entirely consistent [53]. In addition, a study in Europe and another in Asia showed that greenness may attenuate associations between extreme heat and mortality [54,55].…”
Section: Methodssupporting
confidence: 76%
“…Two studies referenced above examined cause-specific mortality, and found that higher levels of NDVI were associated with lower risk of cardiovascular mortality [23,51], but another study [52], did not find an association between NDVI and cardiovascular mortality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the term living wage (or even the word 'wage' makes no appearance)-which seems odd given its connection to positive mental health and the healthy behaviors, (including healthy dietary patterns and opportunity for recreation) which planetary health is attempting to promote [211][212][213][214][215][216][217][218]. Affluent populations might have more true leisure time, and tend to spend more time outside and enjoying nature, because they can afford to [219]. How can an individual establish an emotional connection to nature while working extended hours (or two much-less-than-living-wage jobs!)…”
Section: Academic Planetary Health Expanding the Discoursementioning
confidence: 99%